Continental‐Scale Evidence of Farm Management Impacts on Soil Carbon - Julian Helfenstein; Nick van Dijk; Anna Edlinger; Gabriel Y. K. Moinet; Sophie Q. van Rijssel; Alexandre M. J.‐C. Wadoux; Rachel Creamer; Carmen Vazquez; Vera L. Mulder (Global Change Biology, 2026)
There are high expectations that agricultural practices can mitigate climate change and improve soil health by increasing soil organic carbon (SOC) stocks. However, existing large scale SOC monitoring treats agricultural management as a black box, meaning that observed patterns and trends cannot inform on the option space of agricultural practices to improve or deteriorate SOC stocks. Here, we combine for the first time management data from large scale systematic farm surveys ( n = 248,362 farms) and representative soil monitoring data ( n = 8834 locations) to quantify the impact of agricultural practices on three SOC metrics across all pedoclimatic zones of Europe (EU + UK): stocks, stocks relative to pedoclimatic benchmarks, and yearly change in SOC concentration. Our findings show that in arable and tree crops, but not in grasslands, management intensity is a significant contributor to SOC loss, with impact varying by soil and climate region. However, we also observed that several practices (e.g., high share of manure, organic management, and a high proportion of leys in crop rotation) demonstrated potential for increasing SOC stocks. Under a scenario where all agricultural land in Europe would be managed as that of the 10% most optimally managed farms in terms of SOC benefit, SOC stocks would increase by 1.58 Pg C across Europe (95% CI: 1.27–1.89 Pg C). Whereas under a scenario where farms are managed as the 10% least optimally managed farms, SOC would decrease by −0.92 Pg C (−1.15 to −0.68 Pg C). However, it is important to note that these estimates reflect steady‐state SOC stocks only (i.e., they do not represent the transient build‐up or loss over time, or interactions with a changing climate). This paper thus quantifies how agricultural practices influence patterns in SOC stocks at the continental scale, identifying leverage points for site‐specific policies to improve SOC stocks.

Intercropping and pollination mediate faba bean (Vicia faba ) yield and nodulation - Pibbe Dirkson; Chloé A. Raderschall; Anna Edlinger; Dirk F. van Apeldoorn; Laura G.A. Riggi (Agriculture, Ecosystems & Environment, 2025)

The impact of fungi on soil protist communities in European cereal croplands - Florine Degrune; Kenneth Dumack; Masahiro Ryo; Gina Garland; Sana Romdhane; Aurélien Saghaï; Samiran Banerjee; Anna Edlinger; Chantal Herzog; David S. Pescador; Pablo García‐Palacios; Anna Maria Fiore‐Donno; et al. (Environmental Microbiology, 2024)
Protists, a crucial part of the soil food web, are increasingly acknowledged as significant influencers of nutrient cycling and plant performance in farmlands. While topographical and climatic factors are often considered to drive microbial communities on a continental scale, higher trophic levels like heterotrophic protists also rely on their food sources. In this context, bacterivores have received more attention than fungivores. Our study explored the connection between the community composition of protists (specifically Rhizaria and Cercozoa) and fungi across 156 cereal fields in Europe, spanning a latitudinal gradient of 3000 km. We employed a machine‐learning approach to measure the significance of fungal communities in comparison to bacterial communities, soil abiotic factors, and climate as determinants of the Cercozoa community composition. Our findings indicate that climatic variables and fungal communities are the primary drivers of cercozoan communities, accounting for 70% of their community composition. Structural equation modelling (SEM) unveiled indirect climatic effects on the cercozoan communities through a change in the composition of the fungal communities. Our data also imply that fungivory might be more prevalent among protists than generally believed. This study uncovers a hidden facet of the soil food web, suggesting that the benefits of microbial diversity could be more effectively integrated into sustainable agriculture practices.

Soil microbial biodiversity promotes crop productivity and agro-ecosystem functioning in experimental microcosms - Ferran Romero; Sarah Hilfiker; Anna Edlinger; Alain Held; Kyle Hartman; Maëva Labouyrie; Marcel G.A. van der Heijden (Science of The Total Environment, 2023)

The impact of agricultural management on soil aggregation and carbon storage is regulated by climatic thresholds across a 3000 km European gradient - Anna Edlinger; Gina Garland; Samiran Banerjee; Florine Degrune; Pablo García‐Palacios; Chantal Herzog; David Sánchez Pescador; Sana Romdhane; Masahiro Ryo; Aurélien Saghaï; Sara Hallin; Fernando T. Maestre; et al. (Global Change Biology, 2023)
Organic carbon and aggregate stability are key features of soil quality and are important to consider when evaluating the potential of agricultural soils as carbon sinks. However, we lack a comprehensive understanding of how soil organic carbon (SOC) and aggregate stability respond to agricultural management across wide environmental gradients. Here, we assessed the impact of climatic factors, soil properties and agricultural management (including land use, crop cover, crop diversity, organic fertilization, and management intensity) on SOC and the mean weight diameter of soil aggregates, commonly used as an indicator for soil aggregate stability, across a 3000 km European gradient. Soil aggregate stability (−56%) and SOC stocks (−35%) in the topsoil (20 cm) were lower in croplands compared with neighboring grassland sites (uncropped sites with perennial vegetation and little or no external inputs). Land use and aridity were strong drivers of soil aggregation explaining 33% and 20% of the variation, respectively. SOC stocks were best explained by calcium content (20% of explained variation) followed by aridity (15%) and mean annual temperature (10%). We also found a threshold‐like pattern for SOC stocks and aggregate stability in response to aridity, with lower values at sites with higher aridity. The impact of crop management on aggregate stability and SOC stocks appeared to be regulated by these thresholds, with more pronounced positive effects of crop diversity and more severe negative effects of crop management intensity in nondryland compared with dryland regions. We link the higher sensitivity of SOC stocks and aggregate stability in nondryland regions to a higher climatic potential for aggregate‐mediated SOC stabilization. The presented findings are relevant for improving predictions of management effects on soil structure and C storage and highlight the need for site‐specific agri‐environmental policies to improve soil quality and C sequestration.

Diversity of archaea and niche preferences among putative ammonia‐oxidizing Nitrososphaeria dominating across European arable soils - Aurélien Saghaï; Samiran Banjeree; Florine Degrune; Anna Edlinger; Pablo García‐Palacios; Gina Garland; Marcel G. A. van der Heijden; Chantal Herzog; Fernando T. Maestre; David S. Pescador; Laurent Philippot; Matthias C. Rillig; et al. (Environmental Microbiology, 2022)
Summary Archaeal communities in arable soils are dominated by Nitrososphaeria, a class within Thaumarchaeota comprising all known ammonia‐oxidizing archaea (AOA). AOA are key players in the nitrogen cycle and defining their niche specialization can help predicting effects of environmental change on these communities. However, hierarchical effects of environmental filters on AOA and the delineation of niche preferences of nitrososphaerial lineages remain poorly understood. We used phylogenetic information at fine scale and machine learning approaches to identify climatic, edaphic and geomorphological drivers of Nitrososphaeria and other archaea along a 3000 km European gradient. Only limited insights into the ecology of the low‐abundant archaeal classes could be inferred, but our analyses underlined the multifactorial nature of niche differentiation within Nitrososphaeria. Mean annual temperature, C:N ratio and pH were the best predictors of their diversity, evenness and distribution. Thresholds in the predictions could be defined for C:N ratio and cation exchange capacity. Furthermore, multiple, independent and recent specializations to soil pH were detected in the Nitrososphaeria phylogeny. The coexistence of widespread ecophysiological differences between closely related soil Nitrososphaeria highlights that their ecology is best studied at fine phylogenetic scale.